«Ջուր» բաղադրիչով դարձվածային միավորները հայերենում, ռուսերենում և անգլերենում - Հ. Գ. Պետրոսյան (ՀՀ ԳԱԱ հրատ.)
В основе изучения фразеологизмов с компонентом ”вода” лежит семантическая и структурная характеристика сочетания слов в фразеологических единицах. The present research considers the semantic and structural characteristics of word relation in phraseological units with the component ”water”.
Keywords: Philology; Linguistics; Language and Literature